Direct Synthesis of Perylene‐Fused Cyclic Ketones from Perylene and 2‐Alkenoic Acids. Issue 24 (29th July 2016) - Głodek, Marta; Makal, Anna; Kłys, Arkadiusz; Zakrzewski, Janusz; Plażuk, Damian
Abstract : An efficient, one‐pot methodology of direct synthesis of perylene‐fused cyclic ketones from perylene and 2‐alkenoic acids under acidic catalytic conditions has been developed. The reaction of perylene with 2, 3‐disubstituted 2‐alkenoic acid leads, via Friedel–Crafts acylation followed by Nazarov cyclization, to the formation of disubstituted 5, 6‐dihydro‐4 H ‐cyclopenta[ b ]perylen‐4‐ones in high yield (up to 97 %) and high diastereoselectivity, whereas the reaction with acrylic acid leads, via alkylation followed by intramolecular Friedel–Crafts acylation, to 2, 3‐dihydro‐1 H ‐benzo[ cd ]perylen‐1‐one. Abstract : A direct, efficient synthesis of perylene‐fused cyclic ketones from perylene and 2‐alkenoic acids under acidic catalytic conditions is reported.